Silica nanoparticle–modified paper strip–based new rhodamine B chemosensor for highly selective detection of copper ions in drinking water - Sannok, Tadcha; Wechakorn, Kanokorn; Jantra, Jongjit; Kaewchoay, Netnapit; Teepoo, Siriwan (My University, 2023)
A new rhodamine B derivative (RDB) was synthesized and utilized for the colorimetric detection of copper ions (Cu2+). This chemosensor utilized a paper strip as a support and a smartphone as a detector for on-site quantitative detection of Cu2+ in water samples. Silica nanoparticles (SiNPs) were investigated as the modifier nanoparticles to achieve uniform color on the paper strip and showed a color response 1.9-fold higher than the one without SiNPs. The RDB chemosensor-based paper strip provided high selectivity toward Cu2+ with a detection limit of 0.7 mg/L, and the working concentrations for Cu2+ ranged from 1 to 17 mg/L. Parallel analyses of eight drinking water samples were conducted by inductively coupled plasma optical emission spectroscopy. The results were in good agreement, indicating the practical reliability of the established method with a short assay time and high selectivity. These indicate its great potential for on-site detection of Cu2+. Graphical abstract: [Figure not available: see fulltext.]
Keywords: Chemosensor; Copper ions; Paper strip; Rhodamine B; Silica nanoparticles; Smartphone